Christianity without Christ? David Friedländer’s attempts to establish a religion of reason based on unifying Christianity and Judaism - Schoeps, Julius H. (Nordisk judaistik/Scandinavian Jewish Studies, 2023)
Ever since the publication of Dohm’s Ueber die bürgerliche Verbesserung der Juden (On the Civil Improvement of the Jews) in 1781, which argued for Jewish political equality on humanitarian grounds, more and more voices joined those demands. Prominent among them was David Friedländer, a friend and disciple of Moses Mendelssohn. One of the leading figures of the Berlin Haskalah, he worked towards establishing equal legal status for Jews in Prussia. Friedländer did not accept the given view of his times, the antithesis of Jew and German. For him only the antithesis Jew–Christian existed and even that he tried to reconcile by finding common ground in a religion of reason, the groundwork of which he laid out in an Open Letter in 1799. What he proposed at that time may have been illusionary, but it certainly met with approval in enlightened Jewish circles. Friedländer therefore not only stands for those who dared to break with the traditions, but also for the generation of those who consciously aimed at the denationalization of traditional Judaism – and thus decided in favour of the confessionalization and the Germanness of the Jews.